INVESTIGATE THE PROPERTIES OF DIFFERENT IRRADIATED STARCH BIOPLASTIC FOR PACKAGING APPLICATION - Nurin Najwa Rohidi; Othman, Siti Amira (Malaysian Journal of Science, 2024)
Plastics become the most favourite use among society due to its own characteristics in aspect of barrier properties and strength, we are able to get them anywhere, plus they are cheap, resistible with water and very flexible. Bioplastic produced for the rescue of our environment health. This study aims to determine wettability, contact angle and polymer chemical properties by comparing between pure starch and mixed starches bioplastic with different presence of plasticizer. Materials that will be used in constant amount were distilled water and glycerol. Others will be manipulating variable by the type of presence of starch like corn, potato and rice or maybe mixture of two starches Samples will undergo characterization test such as tensile and elongation test, water contact angle, FTIR analysis, topography using AFM, moisture content test and biodegradability test. When it comes to industrial use, gamma radiation and electron beams are generally involved. The reason for gamma radiation is because gamma rays are extreme in penetration and Cobalt-60 mainly used and often for sterilization purpose. Most of bioplastics with presence of citric acid as addition of plasticizer came out with high contact angle and could achieve hydrophobicity level. Potato and corn-rice bioplastic tend to have low moisture content. Meanwhile, corn bioplastic undergone faster degradation, with 80.17%. Potato-rice with presence of citric acid lead tensile test with 4.095MPa. However, for elongation case, potato with presence of sorbitol lead with 34.57%. From FTIR analysis, functional group of normal polymeric OH stretch and C-H stretch of methylene group were found at wavenumber of 3280-3300 /cm and of 2920- 2935/cm respectively. Through FTIR analysis, corn-rice with presence of citric acid bioplastic were chosen to undergo AFM to survey roughness in case to determine crosslinking might happen, the different average roughness between pre-irradiated and post-irradiatd samples is 8.82 nm.